Accelerating growth and job creation in South Asia - Ghani, Ejaz.(ed.); Ahmed, Sadiq (ed.) (New Delhi, 2009)
In recent times, South Asia has attracted global attention for demonstrating rapid growth. What is not so well known is that this is the least integrated region in the world. South Asia has opened its door to the rest of the world but remains closed to its neighbors. Poor market integration, weak connectivity and a history of conflict have created 'Two South Asia's'. The first is dynamic, urbanized, globally integrated and rapidly growing, the second is rural, impoverished and lagging. Accelerating Growth and Job Creation in South Asia provides fresh perspectives on these issues by exploring the link between regional integration, economic growth and job creation. The outcome of a high-level dialogue between the private sector political leadership, policymakers and academics in South Asia, this volume is an important contribution to the debates in this area.
Keywords: Job creation